Cannabis sativa L. (var. indica) Exhibits Hepatoprotective Effects by Modulating Hepatic Lipid Profile and Mitigating Gluconeogenesis and Cholinergic Dysfunction in Oxidative Hepatic Injury - Erukainure, Ochuko L.; Matsabisa, Motlalepula G.; Salau, Veronica F.; Oyedemi, Sunday O.; Oyenihi, Omolola R.; Ibeji, Collins U.; Islam, Md. Shahidul (Frontiers in Pharmacology, 2021)
Cannabis sativa L. is a crop utilized globally for recreational, therapeutic and religious purposes. Although considered as an illicit drug in most countries, C. sativa until recently started gaining interest for its medicinal application. This study sought out to investigate the hepato-protective effect of C. sativa on iron-mediated oxidative hepatic injury. Hepatic injury was induced ex vivo by incubating hepatic tissues with Fe2+ which led to depleted levels of reduced glutathione, superoxide dismutase, catalase and ENTPDase activities, triglyceride, HDL-C. Induction of hepatic injury also caused significant elevation of malondialdehyde, nitric oxide, cholesterol and LDL-C levels, while concomitantly elevating the activities of ATPase, glycogen phosphorylase, glucose-6-phosphatase, fructose-1,6-biphosphatase, amylase and lipase. Treatment with the hexane, dichloromethane, and ethanol extracts of C. sativa leaves significantly (p<0.05) reversed these levels and activities to almost near normal. However, there was no significant effect on the HDL-C level. The extracts also improved utilization of glucose in Chang liver cells. HPLC analysis showed the presence of phenolics in all extracts, with the ethanol extract having the highest constituents. Cannabidiol (CBD) was identified in all the extracts, while Δ-9-tetrahydrocannabinol (Δ-9-THC) was identified in the hexane and DCM extracts only. Molecular docking studies revealed strong interactions between CBD and Δ-9-THC with the β2 adrenergic receptor of the adrenergic system. The results demonstrate the potential of C. sativa to protect against oxidative-mediated hepatic injury by stalling oxidative stress, gluconeogenesis, and hepatic lipid accumulation while modulating cholinergic and purinergic activity. These activities may be associated with the synergistic effect of the compounds identified and possible interactions with the adrenergic system.